2010
DOI: 10.1111/j.1460-9568.2010.07426.x
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic acid receptor‐α signalling antagonizes both intracellular and extracellular amyloid‐β production and prevents neuronal cell death caused by amyloid‐β

Abstract: Alzheimer’s disease (AD) is characterized by amyloid-β (Aβ) deposition in the brain, neuronal cell loss and cognitive decline. We show here that retinoic acid receptor (RAR)α signalling in vitro can prevent both intracellular and extracellular Aβ accumulation. RARα signalling increases the expression of a disintegrin and metalloprotease 10, an α-secretase that processes the amyloid precursor protein into the non-amyloidic pathway, thus reducing Aβ production. We also show that RARα agonists are neuroprotective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 38 publications
2
60
1
1
Order By: Relevance
“…Several other recent studies have shown that retinoids regulate the expression of many genes involved in the production of Aβ, including BACE-1, PS1, and PS2 [18, 61]. Jarvis and co-workers reported that induction of the RARβ signaling pathway upregulated production of ADAM10, the α-secretase that could process AβPP into a non-amyloidal pathway, thus reducing formation and accumulation of Aβ [65]. Administration of ATRA to the AβPP/PS1 transgenic mice for 2 months was observed to inhibit Aβ aggregation and tau hyperphosphorylation as well as notably improved performance in the Morris water maze test [66].…”
Section: Effects Of Retinoids On Aβ Aggregationmentioning
confidence: 99%
“…Several other recent studies have shown that retinoids regulate the expression of many genes involved in the production of Aβ, including BACE-1, PS1, and PS2 [18, 61]. Jarvis and co-workers reported that induction of the RARβ signaling pathway upregulated production of ADAM10, the α-secretase that could process AβPP into a non-amyloidal pathway, thus reducing formation and accumulation of Aβ [65]. Administration of ATRA to the AβPP/PS1 transgenic mice for 2 months was observed to inhibit Aβ aggregation and tau hyperphosphorylation as well as notably improved performance in the Morris water maze test [66].…”
Section: Effects Of Retinoids On Aβ Aggregationmentioning
confidence: 99%
“…For A␤ staining (6E10), sections were immersed in 70% formic acid for 10 min. The sections were then incubated with primary antibodies to RAR␣ (rabbit IgG, C-20, 1 : 100 dilution; Santa Cruz Biotechnology), RAR␤ (rabbit IgG, C-19, 1 : 100 dilution; Santa Cruz Biotechnology), A␤ [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] (mouse IgG, 6E10, 1 : 500 dilution; Chemicon International, Temecula, CA, USA), Iba1 (rat serum, 1 : 500 dilution; generated against a synthetic peptide corresponding to a specific sequence of mouse Iba1: CNKEHKRPTGPPAKKAISELP (near the C-terminus)), or GFAP (chicken IgY, GTX85454, 1 : 200 dilution; GeneTex), followed by the corresponding Alexa Fluor 488-or 594-labeled secondary antibodies (1 : 300 dilution; Molecular Probes and Abcam). For immunohistochemistry with anti-Iba1 antibody, we used a tyramide signal amplification system (Molecular Probes) according to the manufacturer's recommendations.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…RA increases gene transcription of a disintegrin and metalloprotease, family 10 (ADAM10) [6][7][8] and increases its ␣-secretase activity, which cleaves a specific site of amyloid-␤ protein precursor (A␤PP). This cleavage inhibits A␤ generation and leads to release of the soluble neuroprotective protein sA␤PP␣ [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Decreased intracellular and extracellular Aβ production was reported by Jarvis et al 35) in Tg2576 mice given synthetic retinoid Am580 (1 mg/kg intraperitoneally (i.p.) every 3 d, or 3.6 mg/kg fed daily from 3 to 7 months of age), an isomer of Am80, as a selective RARα agonist (this compound also activates RARβ, but not RARγ or RXRs, like Am80).…”
Section: Amyloid β Etchamendy Et Almentioning
confidence: 99%
“…46) A similar suppression of inflammatory cell death caused by oxidative stress, nitroxide or other stresses seems likely to occur in other brain areas. Jarvis et al 35) reported that Am580 significantly suppressed cell death of cultured cortical neurons exposed to 10 µM Aβ. RA also showed evident suppression of inflammation around sites of aggregation.…”
Section: Suppression Of Inflammationmentioning
confidence: 99%